Prevalence and Diversity of Plant Parasitic Nematodes in Irish Peatlands - Anusha Pulavarty; Tilman Klappauf; Ankit Singh; Patricia Molero Molina; Anique Godjo; Bastiaan Molleman; Douglas McMillan; Thomais Kakouli-Duarte (Diversity)
The prevalence of plant parasitic nematodes (PPN) in the Irish peatlands was investigated in five different peatland habitats—raised bog, cutover scrub/woodlands, fens and peat grasslands, which were further sub-categorised into fourteen different sub-habitats. Within the raised bog habitat were healthy bog hummock (HBH), healthy bog lawn (HBL), degraded bog hummock (DBH) and degraded bog lawn (DBL) and the fen habitats were fen peat (FP) and rich fen peat (R-FP). Cutover scrub or woodland habitat included cutover scrub rewetted (C-RW), cutover scrub non-rewetted (C-NRW), woodlands rewetted (W-RW) and woodlands non-rewetted (W-NRW). Grassland included wasted peat (WP), rough grazing (RG-I) and improved fen peat grassland (IFPG-RW and IFPG-NRW). Soil samples from peatlands were all collected between July and December 2023 when the temperature ranged from 12 to 20 °C. One half of each sample was used for molecular nematode analysis and the other half for morphological identification of nematodes. For the morphological identification, a specific nematode extraction protocol was optimised for peatland soils, and the extracted nematodes were fixed onto slides to be studied under a high-power light microscope. Subsequently, the other part of the soil was processed to isolate total DNA, from which the 18S rRNA gene was sequenced for the identification of nematode taxa. The extracted DNA was also used for randomly amplified polymorphic DNA (RAPD) fingerprinting analysis to determine banding patterns that could classify different bog habitats based on PPN random primers. Compared to that in the climax habitats (HBH, HBL, DBH, DBL, FP, R-FP), PPN prevalence was recorded as being higher in grasslands (WP, RG-I, IFPG-RW and IFPG-NRW) and scrub/woodland ecosystems (C-RW, C-NRW, W-RW, W-NRW). The results indicate that nematode populations are different across the various bog habitats. Emerging and current quarantine PPN belonging to the families Pratylenchidae, Meloidogynidae, Anguinidae and Heteroderidae were noted to be above the threshold limits mentioned under EPPO guidelines, in grassland and wooded peatland habitats. Future actions for PPN management may need to be considered, along with the likelihood that these PPN might impact future paludiculture and other crops and trees growing in nearby agricultural lands.